The Apocalyptic Scriptures - Swanson, Theodore N. (1982)
One of the forms of biblical literature. most difficult to interpret is the one which is called "apocalyptic. n The name derives from the Greek verb apokaluptein, which literally means "to uncover, to unveil," and thus, "to reveal." An apocalypse (Greek apokalupsis, "revelation", "disclosure") is a book which contains the revelation of divine mysteries.
Keywords: Apocalypses; Apocalyptic Eschatology; Apocalyptic in Early Christianity; Apocalyptic in the History of the Church; Apocalyptic today; Apocalypticism